Emerging Molecular Targets for the Treatment of Refractory Sarcoidosis - Boleto, Gonçalo; Vieira, Matheus; Desbois, Anne Claire; Saadoun, David; Cacoub, Patrice (Frontiers in Medicine, 2020)
Sarcoidosis is a multisystem granulomatous disease of unknown origin that has variable clinical course and can affect nearly any organ. It has a chronic course in about 25% of patients. Corticosteroids (CS) are the cornerstone of therapy but their long-term use is associated with cumulative toxicity. Commonly used CS-sparing agents include methotrexate, cyclophosphamide, azathioprine and mycophenolate mofetil. Twenty to 40% of sarcoidosis patients are refractory to these therapies or develop severe adverse events. Therefore, additional and targeted CS-sparing agents are needed for chronic sarcoidosis. Macrophage activation, interferon response, and formation of the granuloma are mainly mediated by T helper-1 responses. Different pro-inflammatory cytokines such as interleukin (IL)-8, IL-12, IL-6 and tumour necrosis factor-alpha (TNF-α) have been shown to be highly expressed in sarcoidosis-affected tissues. As a result of increased production of these cytokines, Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling is constitutively active in sarcoidosis. Several studies of biological agents that target TNF-α have reported their efficacy and appear today as a second line option in refractory sarcoidosis. Some case series report a positive effect of tocilizumab an anti-IL-6 monoclonal antibody in this setting. More recently, JAK inhibition appears as a new promising strategy. This review highlights key advances on the management of chronic refractory sarcoidosis. Novel therapeutic strategies and treatment agents to manage the disease are described.